2019
DOI: 10.1002/pc.25382
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous enhancements of mechanical and thermal properties of monomer cast nylon via polydimethylsiloxane‐modified kaolin

Abstract: Polydimethylsiloxane (PDMS)‐modified Kaolin was prepared by the reaction between kaolin and PDMS. MC nylon 6/kaolin and MC nylon 6/kaolin‐PDMS composites with different filler contents were prepared through in situ polymerization. Thermogravimetric analysis and differential scanning calorimetry analysis show that the feeding of kaolin improved thermal stability and crystallinity of nylon. When 1 wt% addition of kaolin‐PDMS, the tensile strength and impact strength of the as‐prepared composites reached a maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The enhancement of notched impact strength can be explained by the microstructure, which is consistent with the macroscopic performance of the notched impact strength. [ 32 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement of notched impact strength can be explained by the microstructure, which is consistent with the macroscopic performance of the notched impact strength. [ 32 ]…”
Section: Resultsmentioning
confidence: 99%
“…When 1 wt% kaolin‐PDMS was incorporated into OMC nylon, the tensile strength and impact strength of the as‐prepared composites reached maximum values of 77.7 MPa and 4.5 kJ/m 2 respectively. [ 21 ] Similarly, Zhao et al prepared OMC composite materials using graphene oxide and lanthanum (III) chloride (LaCl 3 ) as fillers. The results showed that the composites exhibited excellent comprehensive properties when 0.01 wt% GO and 0.007 wt% LaCl 3 were incorporated in the OMC nylon.…”
Section: Introductionmentioning
confidence: 99%